2020
DOI: 10.18087/cardio.2020.10.n923
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the ultrasonic determination of the degree of interstitial edema in patients with intermediate ejection fraction of the left ventricle after treating acute decompensation of heart failure

Abstract: Aim To study ultrasonic characteristics of lung tissue in patients with heart failure with left ventricular (LV) mid-range ejection fraction (HFmEF) and predictive value of these characteristics after reversing acute decompensated heart failure (ADHF).Material and methods Ultrasonic characteristics of lung tissue were studied by prospective observation in 71 patients (mean age, 65.2±3.6 years; men, 64.3 %) with HFmEF (LVEF from 40 to 49 %) following ADHF reversal. Semiquantitative evaluation of B-lines was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“… 7 It was reported that LUS-BL was related to poor outcome in HFpEF and HFrEF patients. 13 14 In line with results obtained from a small patient cohort, which showed LUS-BL was related to readmission during 2-year follow-up among 71 HFmrEF patients, 10 we found that LUS-BL at admission was independently related to poor CV outcome at 90 days after discharge among ischaemic HFmrEF patients, especially in patients with concomitant hypertension. The results hint that more guideline-directed medical therapies, as shown by up-titration of guideline-directed medical therapies for acute HF (STRONG-HF) trial, which demonstrated that intensive treatment strategy of rapid up-titration of guideline-directed medication and close follow-up after an acute HF admission was readily accepted by patients because it reduced symptoms, improved quality of life and reduced the risk of 180-day all-cause death or HF readmission compared with usual care, 15 might be also helpful to improve the CV outcome of ischaemic HFmrEF patients with LUS-BL>11, especially those with concomitant hypertension.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 7 It was reported that LUS-BL was related to poor outcome in HFpEF and HFrEF patients. 13 14 In line with results obtained from a small patient cohort, which showed LUS-BL was related to readmission during 2-year follow-up among 71 HFmrEF patients, 10 we found that LUS-BL at admission was independently related to poor CV outcome at 90 days after discharge among ischaemic HFmrEF patients, especially in patients with concomitant hypertension. The results hint that more guideline-directed medical therapies, as shown by up-titration of guideline-directed medical therapies for acute HF (STRONG-HF) trial, which demonstrated that intensive treatment strategy of rapid up-titration of guideline-directed medication and close follow-up after an acute HF admission was readily accepted by patients because it reduced symptoms, improved quality of life and reduced the risk of 180-day all-cause death or HF readmission compared with usual care, 15 might be also helpful to improve the CV outcome of ischaemic HFmrEF patients with LUS-BL>11, especially those with concomitant hypertension.…”
Section: Discussionsupporting
confidence: 89%
“…Results showed that the presence of LUS-BL was associated with rehospitalisation up to 2 years after discharge. 10 In this subgroup analysis, we evaluated the prognostic impact of LUS-BL on CV outcome at 90 days and 1-year after discharge in enrolled HFmrEF patients with LUS results at admission. 3 …”
Section: Introductionmentioning
confidence: 99%
“…The results of previous clinical studies on PC status in HFm-rEF patients are sometimes difficult to interpret, since the enrolled "HFmrEF" patients in previous studies are in fact "HFpEF" or "HFrEF" patients per current definition. Skorodumova et al [48] explored PC status in ADHF patients with HFmrEF through LUS. They found that after the remission of ADHF, pulmonary interstitial congestion was still dominant (the distance between B-lines was 7 mm), there was a small amount of pulmonary edema (the distance between B-lines was 3 mm), and the number of B-lines was related to the simultaneous detection of N-terminal pro-Btype natriuretic peptide (NT-proBNP) level and readmission.…”
Section: Pulmonary Congestion In Acute Decompensated Heart Failure Pa...mentioning
confidence: 99%
“…Skorodumova et al . [ 48 ] explored PC status in ADHF patients with HFmrEF through LUS. They found that after the remission of ADHF, pulmonary interstitial congestion was still dominant (the distance between B-lines was 7 mm), there was a small amount of pulmonary edema (the distance between B-lines was 3 mm), and the number of B-lines was related to the simultaneous detection of N-terminal pro-B-type natriuretic peptide (NT-proBNP) level and readmission.…”
Section: Pulmonary Congestion In Acute Decompensated Heart Failure Pa...mentioning
confidence: 99%